81.5k views
0 votes
Which expression represents a simplified form of the expression:

2+3(x-3)+1-5(2-x)?

A. -2x - 16
B. 4x - 11
C. 8x - 16
D. 9x - 23

2 Answers

5 votes

2+3(x-3)+1-5(2-x)=2+3x-9+1-10+5x=3x+5x+2-9+1-10=8x-16

Answer: C.
User Awj
by
5.5k points
3 votes
2+3(x-3)+1-5(2-x)

The first thing we must do is distribute...

2 + 3x - 9 + 1 - 10 + 5x

Then we must combine like terms. We can combine terms with an x together and we can combine terms without an x together.

2 - 9 + 1 - 10 = -16
3x + 5x = 8x

So our simplified expression is C. 8x - 16
User Asiya
by
6.1k points